Processo de criação e espetacularidade da Rainha do Lago Verde do boto Tucuxi no festival dos botos em Santarém-Pará - BELO, Mayanny Xavier (2018)
This work aimed analyze the creation process of Rainha do Lago Verde do Boto Tucuxi, from my experiences during the last seven years, as representing this character, and assuming the condition of ballerina-researcher-interpreter. It also aimed to structure the elements that take part in the item’s construction and correlate them to dance studies, highlighting the spectacles matrixes present in this process, which are essential to the practice studies, as well as, human organized spectacles behavior studies, recognizes as PCHEO, from studies of etnocenology. Authors such as Salles (2006) and Ostrower (1977) were used to discuss the process of creation, and Bião (2007) for studies related to etnocenology, specially to spectacles, theatre and body states; besides Mendes (2010) and Rodrigues (2017) as basis to the dialog about creation processes in dance. The methodology used was etno-research, according to Macedo (2012), and understanding as an auto-investigation and personal description of the universe of the proposed object, while qualitative research. As a result, the spectacular characteristics of Rainha do Lago Verde do Boto Tucuxi is shown.